The Role of Organizational Culture and Emotional Intelligence: Enhancing Healthcare Professionals’ Job Satisfaction - Vasiliki Georgousopoulou; Maria Amanatidou; Pinelopi Vlotinou; Eleni Lahana; Anna Tsiakiri; Ioannis Koutelekos; Eleni Koutra; Georgios Manomenidis (Social Sciences)
Job satisfaction is a critical factor in healthcare settings, influencing both healthcare professionals’ well-being and patient care quality. Nurses, as frontline healthcare professionals, experience various stressors that impact their job satisfaction. Organizational culture (OC) and emotional intelligence (EI) have emerged as significant determinants of nurses’ job satisfaction. However, research on how these factors interact in different cultural contexts remains limited. Objective: This study examines the impact of organizational culture and emotional intelligence on nurses’ job satisfaction. Methods: A descriptive cross-sectional study was conducted among 338 nurses working in secondary and tertiary hospitals in Greece. Data were collected using the Organizational Culture Assessment Instrument (OCAI), Wong and Law Emotional Intelligence Scale (WLEIS), and Job Satisfaction Survey (JSS). Bivariate and multivariate analyses were conducted to explore the associations between job satisfaction and study variables. Results: Nurses reported moderate job satisfaction (JSS mean score = 115.24 ± 20.84). Clan culture was the dominant organizational culture, while Hierarchy culture was the most preferred. EI was recorded at high levels among participants (WLEIS mean = 86.52 ± 12.24). Higher emotional intelligence, permanent employment status, and having children emerged as the most significant predictors of job satisfaction (p < 0.05). Notably, Hierarchy culture did not significantly predict job satisfaction, suggesting that while structure influences satisfaction, it does not solely determine it. Conclusions: The findings emphasize the importance of job security, emotional intelligence, and personal responsibilities in shaping job satisfaction. To enhance satisfaction, healthcare organizations should promote EI training, supportive leadership, and flexible policies that align organizational culture with healthcare professionals’ needs. Further research is needed to explore these relationships in diverse healthcare settings.